Plant volatiles are a salient cue for foraging mammals: elephants target preferred plants despite background plant odour. (September 2019) - McArthur, Clare; Finnerty, Patrick B.; Schmitt, Melissa H.; Shuttleworth, Adam; Shrader, Adrian M.
Abstract : To forage nonrandomly, animals must discriminate among food items. Foods differ in look, smell and taste, providing cues for foragers with appropriate senses. Irrespective of the sensory modality, however, foragers can only use cues effectively if they can detect sensory signals above background noise. Recent evidence shows that foraging mammalian herbivores can detect plant odours, but their capacity to select preferred plants in a noisy olfactory background is unknown. Using choice trials, we tested whether the African elephant, Loxodonta africana, uses plant odour as a salient cue despite increasingly complex and challenging background odours. We first established their preference for familiar plant species. We then tested their capacity to discriminate and select preferred plants based on odour alone. We found that elephants successfully chose preferred species even when presented with complex background odours from nonpreferred plants mimicking multispecies vegetation patches. Elephants also succeeded despite our attempt to mask distinguishing odours with large amounts of a synthetic green leaf volatile. GC–MS analysis confirmed that volatile organic compound profiles differed between plant species. In demonstrating that elephants exploit plant odours even when the signal from preferred plants is embedded in sensory noise of background odours, we provide crucial behavioural evidence that olfaction provides an efficient mechanism for selective, nonrandom foraging. Whether mammalian herbivores recognize novel odours, for example from newly invading plant species, or when air pollution degrades odours of familiar plants, needs investigating. Accounting for the capacity of mammalian herbivores to use plant odour cues will improve models of both their foraging behaviour and the ecosystem impacts of their foraging. Highlights: Elephants choose preferred plants using odour cues alone. Odour cues are useful even when mixed with odours from other plants. An abundant green leaf volatile fails to mask odour cues of preferred plants. Olfaction probably plays a key role in efficient foraging by mammalian herbivores.